2017
DOI: 10.3892/mmr.2017.7998
|View full text |Cite|
|
Sign up to set email alerts
|

Roles and mechanisms of TRPC3 and the PLCγ/PKC/CPI-17 signaling pathway in regulating parturition

Abstract: The aim of the current study was to investigate the role of phospholipase C (PLC)γ/protein kinase C (PKC)/C-kinase-activated protein phosphatase-1 (CPI-17) signaling pathways in uterine smooth muscle during parturition. Samples of uterine tissue were collected from pregnant patients who underwent a caesarean section for preterm delivery, full-term delivery with labor onset, full-term delivery without labor onset, and from a non-pregnant control group undergoing surgery for cervical intraepithelial neoplasia II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…This process has a key role in regulating intracellular Ca 2+ through multiple Ca 2+ channels [103,104,105]. PLCγ/PKC is also involved in the regulation of cell proliferation, contraction and migration [106,107,108].…”
Section: Receptor Tyrosine Kinase Signaling and Mg2+mentioning
confidence: 99%
“…This process has a key role in regulating intracellular Ca 2+ through multiple Ca 2+ channels [103,104,105]. PLCγ/PKC is also involved in the regulation of cell proliferation, contraction and migration [106,107,108].…”
Section: Receptor Tyrosine Kinase Signaling and Mg2+mentioning
confidence: 99%
“…More importantly, the increased miR-25-3p level injured the contractile function of the heart muscle cells via the suppression of SERCA2a [ 24 ]. The expression of the T-type calcium channel protein Cav3.2 was increased in the uterine smooth muscle of pregnant rats [ 21 ]; we further found that the Cav3.2 was overexpressed in the myometrial smooth muscle of infected preterm mice [ 53 ] and the disturbance of the Cav3.2 pathway attenuated absolute contraction of cells [ 54 ]. Thus, we aimed to define whether miR-25-3p participates in PTL by regulating HMSM contraction in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…AtPI-PLC6 , AtPI-PLC7 , and AtPI-PLC8 were up-regulated by auxin and cytokinin [ 9 , 31 ]. In other plants, the expression of mung bean VrPI-PLC3 , tobacco NtPI-PLC1 , potato StPI-PLC1 , and StPI-PLC2 , and tempeh bean TluPI-PLC1 and TluPI-PLC2 was influenced by drought stress [ 38 , 39 , 40 , 41 ]. In our study, the results of qRT-PCR showed that the TaPLC genes were responsive to drought, salt, and cold stress.…”
Section: Discussionmentioning
confidence: 99%